2020
DOI: 10.2139/ssrn.3713732
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Resilience Hope and Adaptability as Protective Factors in Times of Crisis: A Study in Greek and Cypriot Society during the COVID-19 Pandemic

Abstract: Various studies have assessed resilience in relation to risk and protective factors during periods of crisis, and have shown that values such as hope and optimism are significantly related to peoples' level of quality of life in times of crisis. The Covid-19 pandemic has proven to be a great challenge as it is an unprecedented global health crisis. Our study aims to explore the effects of psychological resilience, hope, and adaptability when people experience real or perceived possible danger. The present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
0
5
1
Order By: Relevance
“…Demetriou et al also concluded that resilience has a positive relation with age; as age advances, resilience appears to increase. 66 Contrary to our results, Klein et al exhibited that the perceived stress was higher in younger age groups, correlated with another study carried out in India. 67,68 A study conducted in the Philippines discovered that young generations are dealt with higher psychological aftermath from the ongoing pandemic than men, respectively.…”
Section: Discussioncontrasting
confidence: 94%
“…Demetriou et al also concluded that resilience has a positive relation with age; as age advances, resilience appears to increase. 66 Contrary to our results, Klein et al exhibited that the perceived stress was higher in younger age groups, correlated with another study carried out in India. 67,68 A study conducted in the Philippines discovered that young generations are dealt with higher psychological aftermath from the ongoing pandemic than men, respectively.…”
Section: Discussioncontrasting
confidence: 94%
“…A possible explanation for this association is that resilience can emerge as the ability to take full advantage of their positive personal characteristics despite stressful occupational circumstances. Moreover, healthcare providers’ experiences in providing care for COVID-19 patients and their family members, their access to expert colleagues and resources, their psychological knowledge, and their relatively high level of education [ 28 ] may help them to cope with psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, survey studies showed that resilience had a negative association with psychological distress among physicians [ 26 ] and with depressive symptoms in the general population [ 27 ]. Factors contributing to resilience were found to include greater age and higher educational level [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…A higher level of resilience could make students happier and improve their life on some aspects such as feeling more optimistic, peaceful, clear-minded, and energetic ( Huerta et al, 2021 ). Also, individuals with higher resilience showed higher adaptability and better coping under the pandemic ( Demetriou et al, 2020 ). As for emotional competence, excellent ability to self-regulate thoughts and emotions leads to increased well-being ( Huerta et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%